Tamanho de partícula do volumoso e frequência de alimentação sobre aspectos nutricionais e do metabolismo energético em ovinos - Silas Primola Gomes (2008)
The effect of particle size of the forage and frequency of feed on the nutrition and energy metabolism of sheep were evaluated trough four experiments: Experiment 1 – Intake (I), apparent digestibility (AD) and ingestive behavior were studied in sheep fed in two daily frequencies and four particle size of forage. Twenty-four sheep with live weight (LW) of 37.0 kg were studied in completely randomized design in factorial 2x4 scheme. Tifton-85 hay and a commercial concentrate were used with a ratio of 25:75%, respectively. The responses of intake and AD were not modified with treatments (P>0,05). Dry matter intake (DMI) was 97.43 g/day/kgW0,75 and DMDA was 66.12%. The intake of neutral detergent fiber (NDFI) was 47.2 g/day/ kgW0,75. Smaller particle size (2 mm) had smaller times of rumination (214.58 minutes/day) and chewing activity (360.41 minutes/day) (P<0.05). Animals spent 423.48 minutes/day/kg of NDFI in rumination and 676.19 minutes/day/kg of NDFI in chewing activity. The times spent with rumination and the total chewing activity in sheep are lowered with reducing the particle size of the forage. The particle size of the forage and frequency of feed did not affect the I and AD in sheep. Experiment 2 – Eight sheep with live weight (LW) of 52.5 kg were studied in completely randomized blocks design in factorial 2x4 scheme, fed in two daily frequencies (twice or four times) and four particle size (2, 5,10 and 25 mm) of forage. Tifton-85 hay and a commercial concentrate were used with a ratio of 25:75%, respectively. Passage of digesta particles from the rumen was in average 2.37%/h. The retention time in the rumen was 86.86h and retention time in the digestive tract was 90.52h. Animals fed with smaller particle size (2 mm) had lower ruminal pH (6.13) (P<0.05) and average of ruminal pH was 6.25 for other particle size. Animals fed in daily frequency of four times had lower ruminal pH (6.17) (P<0.05) than animals fed twice for day (pH 6,26). Particle size of 2mm and daily frequency of four times reduces ruminal pH. Experiment 3 – In situ degradability of dry matter (DM) and neutral detergent fiber (NDF) of Tifton-85 hay with different particle size (2 mm; 5 mm; 10 mm and 25 mm) in sheep supplemented or not with concentrate (0 or 75% of concentrate) were determined. Incubation times were 0, 6, 12, 24, 48, 72 and 96 hours. Completely randomized blocks design in factorial 2x4 schemes (two diets and four particle size of forage) with split-plot was used. The smaller particle size (2 mm) had higher values of soluble fraction and effective degradability of DM and NDF in the two diets fed. DM in situ disappearance was higher for 2mm particle size (P<0.05). Particle size of forage and diet influenced degradation parameters and disappearance rate of DM an NDF, thus it is important the standardization of this variables studied on in situ degradation in sheep. Experiment 4 – Eight sheep with live weight of 52.5 kg were studied in completely randomized blocks design in factorial 2x4 scheme, fed in two daily frequencies and four particle size of forage. Tifton-85 hay and a commercial concentrate were used with a ratio of 25:75%, respectively. Respiration calorimetry work was carried using an open circuit respiration chamber for small ruminants. The oxygen (O2), carbonic gas (CO2), methane (CH4) and urinary nitrogen (URN) levels were determined and used in body heat production (HP) determination. The retained nitrogen (N) was 0.63 g/day/kg MW (metabolic weight). This value was 36.0% of N intake and 46.84% of absorbed N. The HP was 40.0% of gross energy intake (GEI). The energy loss as CH4 was 4.88% of gross energy (GE) and 5.94% of digestible energy (DE). The metabolizable energy (ME) was 73.24% of GEI and the net energy (NE) of diets was 1.807.35 kcal/day. Feeding frequency and particle size of forage didn’t have effect on nitrogen balance and energy metabolism of sheep.